Noncommutative spectral geometry and the deformed Hopf algebra structure of quantum field theory - Sakellariadou, Mairi; Stabile, Antonio; Vitiello, Giuseppe (arXiv.org, 2013)
We report the results obtained in the study of Alain Connes noncommutative spectral geometry construction focusing on its essential ingredient of the algebra doubling. We show that such a two-sheeted structure is related with the gauge structure of the theory, its dissipative character and carries in itself the seeds of quantization. From the algebraic point of view, the algebra doubling process has the same structure of the deformed Hops algebra structure which characterizes quantum field theory.